Sixty-six million years along the road of mammalian ecomorphological specialization. - Figueirido-Castillo, Francisco Borja; Palmqvist-Barrena, Carlos Paul; Pérez-Claros, Juan Antonio; Janis, Christine Marie (Proceedings of the National Academy of Sciences of the United States, 2019)
The fossil record of the large terrestrial mammals of the NorthAmerican Cenozoic has previously been quantitatively summarizedin six sequential episodes of faunal associations—“evolutionary faunas”—that correspond well with previously proposed qualitative“Chronofaunas.”Here, we investigate the ecological spectrum ofthese faunas by classifying their major taxonomic components intodiscrete ecomorphological categories of diet, locomotion, and bodysize. To specifically address the potential influence of long-termclimatic shifts on the ecomorphological composition of these faunas,we analyze via contingency tables and detrended correspondenceanalyses the frequency distribution of ecomorph types within fau-nas. We show that each evolutionary fauna has a unique, nonran-dom association of ecomorphs, and we identify a long-term trendtoward greater ecomorphological specialization over successive fau-nas during the past 66 My. Major vegetation shifts induced by cli-matic changes appear to underlie the ecomorphological dynamics ofthese six temporal associations that summarize Cenozoic NorthAmerican mammalian evolutionary history.
Open acess (ce 31/01/24)
Keywords: Paleontología - Cenozoico; Mamíferos fósiles - Cenozoico; Paleoclimatología - Cenozoico; Cenozoic mamals; Ecomoprhology; Evolutionary faunas; Cenozoic climate change